Study of the physicochemical characteristics, antimicrobial activity, and in vitro multiplication of wild blackberry species from the Peruvian highlands - Lapiz Culqui, Yoiner K. (2024)
The Peruvian Andes are the natural habitat of several wild blackberry species that are little known and exploited due to the lack of technological and scientific development to support their agricultural potential. In this context, a study was conducted to understand the physicochemical composition, bioactive compounds, antimicrobial activity, and in vitro multiplication of four wild blackberry (Rubus sp.) species from the northern Peruvian highlands. The results indicate that fruits of R. floribundus presented the highest content of total soluble solids (9.58 ± 1.83°Brix) and titratable acidity (1.88 ± 0.07% citric acid). The fruits of R. weberbaueri recorded the highest total phenolic content (415.06 ± 8.69 mg GAE/100 g Ff). The antioxidant capacity determined by the DPPH assay varied significantly among species, with the highest value found in fruits of R. andicola (50.27 ± 0.11 mg TE/100 g Ff). The fruit extracts of R. weberbaueri and R. andicola showed better antimicrobial activity, with Staphylococcus aureus being the most sensitive bacterium. In the in vitro multiplication phase, the results show that BAP (6-Benzylaminopurine) has a significant effect at a dose of 1.5 mg l−1 on shoot number, leaf number, and shoot length. The results may help in the management of genetic resources.